Memverifikasi Hukum Hooke dalam Laboratorium Fisika Sarjana: Sebuah Studi Eksperimental dengan Penekanan pada Kesadaran Ketidakpastian Pengukuran - Tri; Putri; Jeliana (Universitas Garut, 2026)
This study aims to experimentally verify Hooke’s Law and examine the elastic characteristics of a metal spring within its elastic region. A laboratory experimental method with a descriptive quantitative approach was employed by applying incremental loads of 50–80 g, where each load was measured through three repeated trials (n = 3) to improve data reliability. The resulting elongation was analyzed using linear regression between applied force and elongation. The results show a strong linear relationship, yielding an average spring constant of approximately 2.9 N/m, with the regression equation and a coefficient of determination close to 1.00, indicating high linearity. Measurement uncertainties arose primarily from instrument resolution (±0.5 mm) and possible parallax errors; however, these variations remained within acceptable limits and did not significantly affect the linear trend. These findings confirm that the spring operated within its elastic region and empirically support Hooke’s Law. The study also highlights the pedagogical value of experimental activities in enhancing students’ understanding of elasticity concepts and awareness of measurement uncertainty.